Polymorphism of XRCC7 Gene and Risk of Glioma: A Prospective Case–Control Study - Deepak Choudhary; Bhawna Mahajan; Mamta Sumi; Binita Dholakia; Sumit Bhandari; Niraj Ghimire; Sundeep Saluja; Shaam Bodeliwala; Wajid Nazir Wani; Anita Jagetia (Indian Journal of Neurosurgery)
Objective The aim of this study is to determine association between polymorphism of XRCC7 gene and glioma.